Associations between serum cholesterol and immunophenotypical characteristics of circulatory B cells and Tregs - Schmitz, Timo; Freuer, Dennis; Linseisen, Jakob; Meisinger, Christa (Journal of lipid research, 2023)
Blood lipids play a major role in the manifestation of cardiovascular diseases. Recent research suggested that there are connections between cholesterol levels and immunological alterations. We investigated whether there is an association between serum cholesterol levels (total, HDL, and LDL) and immune cells (B cell and regulatory T cells [Tregs]). The analysis was based on data from 231 participants of the MEGA study in Augsburg, Germany, recruited between 2018 and 2021. Most participants were examined two different times within a period of 9 months. At every visit, fasting venous blood samples were taken. Immune cells were analyzed immediately afterward using flow cytometry. Using multivariable-adjusted linear regression models, the associations between blood cholesterol concentrations and the relative quantity of several B-cell and Treg subsets were analyzed. We found that particularly HDL cholesterol concentrations were significantly associated to some immune cell subpopulations: HDL cholesterol showed significant positive associations with the relative frequency of CD25++ Tregs (as proportion of all CD4+CD25++ T cells) and conventional Tregs (defined as the proportion of CD25+CD127− cells on all CD45RA−CD4+ T cells). Regarding B cells, HDL cholesterol values were inversely associated with the cell surface expression of IgD and with naïve B cells (CD27−IgD+ B cells). In conclusion, HDL cholesterol levels were associated with modifications in the composition of B-cell and Treg subsets demonstrating an important interconnection between lipid metabolism and immune system. Knowledge about this association might be crucial for a deeper and more comprehensive understanding of the pathophysiology of atherosclerosis.